Albumin Oxidation Status in Sepsis Patients Treated With Albumin or Crystalloids - Bonifazi, Matteo; Meessen, Jennifer; Pérez, Alba; Vasques, Francesco; Busana, Mattia; Vassalli, Francesco; Novelli, Deborah; Bernasconi, Roberto; Signori, Chiara; Masson, Serge; Romitti, Federica; Giosa, Lorenzo; et al. (Frontiers in Physiology, 2021)
Inflammation and oxidative stress characterize sepsis and determine its severity. In this study, we investigated the relationship between albumin oxidation and sepsis severity in a selected cohort of patients from the Albumin Italian Outcome Study (ALBIOS). A retrospective analysis was conducted on the oxidation forms of human albumin (human mercapto-albumin (HMA), human non-mercapto-albumin form 1 (HNA1) and human non-mercapto-albumin form 2 (HNA2)) in 60 patients with severe sepsis or septic shock and 21 healthy controls. The sepsis patients were randomized (1:1) to treatment with 20% albumin and crystalloid solution or crystalloid solution alone. The albumin oxidation forms were measured at day 1 and day 7. To assess the albumin oxidation forms as a function of oxidative stress, the 60 sepsis patients, regardless of the treatment, were grouped based on baseline sequential organ failure assessment score (SOFA) as surrogate marker of oxidative stress. At day 1, septic patients had significantly lower levels of HMA and higher levels of HNA1 and HNA2 than healthy controls. HMA and HNA1 concentrations were similar in patients treated with albumin or crystalloids at day 1, while HNA2 concentration was significantly greater in albumin-treated patients (p < 0.001). On day 7, HMA was significantly higher in albumin-treated patients while HNA2 significantly increased only in the crystalloid-treated group, reaching values comparable with the albumin group. When pooling the septic patients regardless of treatment, albumin oxidation was similar across all SOFA groups at day 1, but at day 7 HMA was lower at higher SOFA scores. Mortality rate was independently associated with albumin oxidation levels measured at day 7 (HMA log-rank=0.027, HNA2 log-rank=0.002), irrespective of treatment group. In adjusted regression analyses for 90-day mortality, this effect remained significant for HMA and HNA2. Our data suggest that the oxidation status of albumin is modified according to the time of exposure to oxidative stress (differences between day 1 and day 7). After 7 days of treatment, lower SOFA scores correlate with higher albumin antioxidant capacity. The trend toward a positive effect of albumin treatment, while not statistically significant, warrants further investigation.